Systematic Review of Injuries in the Men's and Women's National Basketball Association. Issue 5 (April 2022) - Lian, Jayson; Sewani, Faraz; Dayan, Isaac; Voleti, Pramod B.; Gonzalez, David; Levy, I. Martin; Musahl, Volker; Allen, Answorth
Background: Numerous studies have reported the incidence and outcomes of injuries in the men's and women's National Basketball Association (NBA and WNBA, respectively). Purpose: To synthesize published data regarding the incidence and outcomes of all injuries in the NBA and WNBA in a comprehensive review. Study Design: Systematic review; Level of evidence, 4. Methods: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched 3 electronic databases (PubMed, MEDLINE, Embase) for studies of all levels of evidence since 1990 pertaining to injuries sustained by active players in the NBA and WNBA. Studies were excluded if the cohort of interest included ≤3 active players. Results: The initial search of the 3 databases yielded 1253 unique studies, of which 49 met final inclusion criteria for this review. Only 4 studies included athletes in the WNBA. Based on the mean annual incidence, the 5 most common orthopaedic sports injuries sustained in the NBA were concussions (9.5-14.9 per year), fractures of the hand (3.5-5.5 per year), lower extremity stress fractures (4.8 per year), meniscal tears (2.3-3.3 per year), and anterior cruciate ligament tears (1.5-2.6 per year). Cartilage defects treated using microfracture, Achilles tendon ruptures, and anterior cruciate ligament injuries were 3 injuries that led to significant reductions in performance measurements after injury. Conclusion: With advances in sports technology and statistical analysis, there is rapidly growing interest in injuries among professional basketball athletes. High-quality prospective studies are needed to understand the prevalence and effect of injuries on player performance and career length. This information can inform preventative and treatment measures taken by health care providers to protect players and guide safe return to play at a high level.